Legal Protection For Policyholders Concering Insurance Companies Restructuring In Default - Indra Rukmana, Frisca (International Significance of Notary, 2023)
Abstract : Financial Management in an insurance company has been regulated in the Financial Services Authority Regulation (POJK) Number 71 / POJK.05 / 2016 which regulates an assessment of the health of insurance and reinsurance companies in Indonesia. In the case of default, the insurance company in restructuring has a restructuring option, but the restructuring has a significant impact on the customer, but the insurance policyholder customer can ask for legal protection and justice in terms of the return of compensation experienced. This legal protection is based on authentic evidence, that is, an insurance policy. In the context of insurance company restructuring, legal protection for policyholders may also involve financial supervisory institutions, such as the Financial Services Authority (OJK). The research method used in this study is normative legal research, which uses the statutory approach (statute approach) and conceptual approach (conceptual approach). The legal materials used are primary, secondary and tertiary legal materials. The legal material collection techniques used are primary, secondary and tertiary legal material collection techniques. Legal protection for policyholders in the event of default by the insurance company Policyholders can take legal action through non-litigation means such as mediation or litigation in court. The legal protection of policyholders is regulated in the Insurance Law.Keywords: Legal Protection, Restructuring, Insurance, Default